Management of adverse events during treatment of gastrointestinal cancers with epidermal growth factor inhibitors - Hofheinz, Ralf-Dieter (Critical reviews in oncology, hematology, 2017)
The epidermal growth factor receptor (EGFR) is involved in development and progression of some gastrointestinal cancers, and is targeted by monoclonal antibodies (mAbs) and tyrosine kinase inhibitors (TKIs) used to treat these conditions. Targeted agents are generally better tolerated than conventional chemotherapy, but have characteristic toxicities that can affect adherence, dosing, and outcomes. Skin conditions are the most common toxicities associated with EGFR inhibitors, particularly papulopustular rash. Other common toxicities include mucosal toxicity, electrolyte imbalances (notably hypomagnesaemia), and diarrhoea, while the chimaeric mAb cetuximab is also associated with increased risk of infusion reactions. With appropriate prophylaxis, the incidence and severity of these events can be reduced, while management strategies tailored to the patient and the degree of toxicity can help to ensure continuation of anti-cancer therapy. Here, we review the main toxicities associated with EGFR-inhibiting mAbs and TKIs in patients with gastrointestinal cancers, and provide recommendations for prophylaxis and treatment.